How Customer Value and Customer Self Construal Influence Repurchase Intentions Moderated by Customer’s Country Origin: Study of Gen Z in Indonesia-Malaysia - Sudaryanto, Sudaryanto; Irawan, Bambang; Dewi, Ivana Rosediana; Hanim, Anifatul; Istiyani, Nanik; ., Rusdiyanto (Journal of Ecohumanism, 2024)
This research aims to analyse the influence of Customer (perceived) Value and Self-construal in Gen Z on their decision to repurchase fashion products online in e-commerce such as e-Matahari, Zalora, and Pomelo, with country of origin as the moderating variable. This research uses the SEM-PLS method with SmartPLS software to analyse 236 data generated from online questionnaires to consumers in Indonesia and Malaysia. This research variable was determined after conducting text mining analysis using the orange application, which produces keywords and sentiment analysis to become a reference in deciding variables. The results of the study show that Customer (perceived) Value and Self-construal are directly able to influence Repurchase Intention significantly. At the same time, the country of origin cannot moderate this influence.